THE CULTURAL HERITAGE OF THE OLD BELIEVERS IN THE SOCIO-CULTURAL SPACE OF TRANSBAIKALIA - Tatiana V. Mishina; Natalia S. Kondakova (Russian Studies in Culture and Society)
Background. The socio-cultural space of Transbaikalia is represented by a wide ethno-cultural diversity, which was formed historically under the influence of various factors. Subsequently, each of the cultures that appeared in Transbaikalia contributed to the cultural space of the region. However, today there is a change in the importance of traditional cultures, new values appear that are more in demand in modern conditions, hence the loss of traditional culture, the disappearance of cultural heritage. The issue of preservation and transmission of traditional culture is becoming urgent.